Induction of apoptosis in cerebellar granule neurons by low potassium: inhibition of death by insulin-like growth factor I and cAMP. - D'Mello, S R (1993)
High levels of extracellular K+ ensure proper development and prolong survival of cerebellar granule neurons in culture. We find that when switched from a culture medium containing high K+ (25 mM) to one containing a low but more physiological K+ concentration (5 mM), differentiated granule neurons degenerate and die. Death induced by low K+ is due to apoptosis (programmed cell death), a form of cell death observed extensively in the developing nervous system and believed to be necessary for proper neurogenesis. The death process is accompanied by cleavage of genomic DNA into internucleosome-sized fragments, a hallmark of apoptosis. Inhibitors of transcription and translation suppress apoptosis induced by low K+, suggesting the necessity for newly synthesized gene products for activation of the process. Death can be prevented by insulin-like growth factor I but not by several other growth/neurotrophic factors. cAMP but not the protein kinase C activator phorbol 12-myristate 13-acetate can also support survival in low K+. In view of the large numbers of granule neurons that can be homogeneously cultured, our results offer the prospect of an excellent model system to study the mechanisms underlying apoptosis in the central nervous system and the suppression of this process by survival factors such as insulin-like growth factor I.